Optimization of air supply location, size, and parameters in enclosed environments using a computational fluid dynamics-based adjoint method. Issue 2 (3rd March 2016) - Liu, Wei; Jin, Mingang; Chen, Chun; Chen, Qingyan
Abstract : Optimal design of an indoor environment based on specific design objectives requires a determination of thermo-fluid control methods. The control methods include the air supply location, size, and parameters. This study used a computational fluid dynamics- (CFD) based adjoint method to identify the optimal air supply location, size, and parameters. Through defining the air distribution in a certain area (design domain) as a design objective in a two-dimensional, ventilated cavity, the adjoint method can identify the air supply location, size, and parameters. However, the air supply location, size, and parameters were not unique, which implied multiple solutions. By using any of the air supply location, size, and parameters identified as boundary conditions for forward CFD simulations, the computed air distribution in the design domain was the same as that used as a design objective. Thus, the computing costs did not depend on the number of design variables.